EXPLORING THE BENEFITS OF CREATINE SUPPLEMENTATION IN STRENGTH TRAINING AND HYPERTROPHY (CIPEEX, 2025)
Creatine, a substance found naturally in the human body and present in foods such as red meat and fish, has gained prominence as one of the most studied and used supplements in sports. Its role in improving athletic performance, especially in short-duration, high-intensity activities, has been extensively researched in recent decades.This study examines the main mechanisms of action of creatine and its potential benefits for strength training and hypertrophy. Data from studies conducted between 2014 and 2024, available in the Medline database, were analyzed using keywords such as creatine supplementation, power, strength, hypertrophy, muscle mass, and lean mass.Creatine supplementation has shown potential effects on gene expression and muscle trophism pathways, including osmotic regulation, glycogen metabolism, cytoskeleton remodeling, and satellite cell activity. The ergogenic effects of creatine, such as increased water retention, protein translation efficiency, and satellite cell activation, contribute to improved muscle strength and hypertrophy.Although the exact mechanisms remain under investigation, studies highlight the significant role of creatine in muscle function and growth. This research underscores the importance of updated usage guidelines and continued exploration of creatine's potential benefits.
Keywords: Creatine; Training; Supplement